2017
DOI: 10.1177/0255761417712318
|View full text |Cite
|
Sign up to set email alerts
|

Shaping interpersonal learning in the jazz improvisation lesson: Observing a dynamic systems approach

Abstract: Music institutions predominantly utilize the one-to-one lesson in developing and supporting music students’ learning of skill and knowledge. This article explores the effect that interpersonal interaction plays in shaping pedagogical applications between teacher and student. Observing the learning of improvisation within this individualized social context, dynamic systems theory (DST) is used to explore how learning and development of musical improvisation skills are shaped by interpersonal behaviors and learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Within the one-to-one teaching environment Burwell (2012) has investigated prevailing teaching cultures, and ( de Bruin, 2017 , 2018d ) has reported on the significance of interpersonal dimensions in the teacher-student learning relationship. Within this learning domain, salient aspects of teacher interaction point to the influence of verbal interactions on performance behavior ( Folkestad, 2005 ), the impact of verbally prompted behavior involving engaging dialogue ( Anderson et al, 2011 ), inclusive teacher actions that activate participation of students in their learning ( Carey and Grant, 2014 ), and confluence of teacher-student goals and aims ( de Bruin, 2018c ) pointing to the more refined facets of the inter- and intra-psychological connectivity that promotes how teachers and students come to know “each other’s minds” in the music lesson ( Bruner, 1996 , p. 12).…”
Section: Introductionmentioning
confidence: 99%
“…Within the one-to-one teaching environment Burwell (2012) has investigated prevailing teaching cultures, and ( de Bruin, 2017 , 2018d ) has reported on the significance of interpersonal dimensions in the teacher-student learning relationship. Within this learning domain, salient aspects of teacher interaction point to the influence of verbal interactions on performance behavior ( Folkestad, 2005 ), the impact of verbally prompted behavior involving engaging dialogue ( Anderson et al, 2011 ), inclusive teacher actions that activate participation of students in their learning ( Carey and Grant, 2014 ), and confluence of teacher-student goals and aims ( de Bruin, 2018c ) pointing to the more refined facets of the inter- and intra-psychological connectivity that promotes how teachers and students come to know “each other’s minds” in the music lesson ( Bruner, 1996 , p. 12).…”
Section: Introductionmentioning
confidence: 99%
“…Within the dynamic and complex social world of musical training in the conservatoire, learners evolve, adapt and self-regulate behaviour within vibrant and dynamic learning communities (de Bruin, 2016). Students self-regulate individually, co-regulate with teachers in the one-to-one lesson, as well as socially share regulation of learning within ensembles (de Bruin, 2017b). Learner processes consider ‘reflection in action’, whereby students acquire knowing-in-action under the tutelage of expert practitioners, and ‘reflection on action’, the deliberate review of one’s actions on observed or experienced outcomes (Schön, 1983).…”
Section: Sct and Regulation Of Learningmentioning
confidence: 99%
“…High-quality learning relationships allow individuals not only to learn that certain beliefs are useful for functioning in particular environments, but that they actually internalize those valued by teachers and become part of the individual’s own belief system (Wentzel, 1999). In a music-learning context, good interpersonal relationships with a particular instrumental teacher or exponent of improvisation are likely to lead students to internalize at least some of that teacher’s beliefs and values about how to learn, sound, conceptualize and act (de Bruin, 2017b). Learning is supported through both ‘hard’ and ‘soft’ scaffolds (Saye & Brush, 2002), static hard supports such as reading and rote learning of technical exercises, and dynamic ‘soft’ supports built from developing interaction.…”
Section: The Impact Of Learning Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning to improvise rarely occurs in isolation, but rather is shaped and guided by the pedagogical orientations of a teacher (Berliner, 1994). Furthermore, the nature of the relationship between student and teacher has direct bearing on student’s musical development (de Bruin, 2016, 2017a, 2017b). De Bruin’s (2017a, 2017b) investigations into the interactive relationship between students and teachers in a one-on-one setting revealed modeling, scaffolding, and coaching as explicit techniques used by his participants.…”
Section: Tensions In Jazz Pedagogymentioning
confidence: 99%